2017
DOI: 10.1038/srep42486
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism and evolutionary differentiation of Eastern Chinese Han: a comprehensive and comparative analysis on KIRs

Abstract: Killer cell immunoglobulin-like receptor genes, namely KIRs, cluster together within the 160 kb genomic DNA region. In this study, we used PCR-SSP approach and successfully identified the genotype of 17 KIR genes in 123 independent healthy donors residing in the Jiangsu province, China. All individuals were positive at the 7 genes. The observed carrier gene frequencies (OFs) of remaining 10 KIRs ranged from 14.63% (KIR2DS3) to 95.93% (KIR3DL1). We found 27 distinct genotypes excluding KIR1D. The most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
2
4
1
Order By: Relevance
“…Here, we compared the distribution of the high‐frequency KIR genotype profiles (>1.0) within Han populations, and with other worldwide populations (Table ). The top four high‐frequency KIR genotype profiles (AA, Bx2, Bx8, and Bx4) found in the present population were consistent with other studies on Han population . The frequencies reported for the other five genotype profiles with high frequencies (Bx3, Bx9, Bx5, Bx75, and Bx6) are slightly different between the Han populations which may be caused by sample size.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Here, we compared the distribution of the high‐frequency KIR genotype profiles (>1.0) within Han populations, and with other worldwide populations (Table ). The top four high‐frequency KIR genotype profiles (AA, Bx2, Bx8, and Bx4) found in the present population were consistent with other studies on Han population . The frequencies reported for the other five genotype profiles with high frequencies (Bx3, Bx9, Bx5, Bx75, and Bx6) are slightly different between the Han populations which may be caused by sample size.…”
Section: Resultssupporting
confidence: 89%
“…KIR GFs in the studied population were compared with other populations, as shown in Table 1. The results are similar to the data reported by other studies on Han, [12][13][14][15] showing we obtained the KIR gene distribution of the Eastern Han population. The KIR gene distribution of the Eastern Han is similar to that of the Japanese 24 but different from that of other Asian populations.…”
Section: Kir Genes In the Populationsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, infertile patients who carry the KIR A haplotype experienced fewer pregnancy losses following euploid single-embryo transfer compared with KIR B haplotype carriers ( 28 ). In the Han Chinese population, the KIR AA genotype has a high prevalence, which may reach up to half of the total number of the population in some areas ( 47 ), however, no difference was identified in the frequency of the KIR AA genotype between the two groups in the present study. The rate of the BB genotype was significantly higher in women who had aborted ≥3 times compared with the control group.…”
Section: Discussioncontrasting
confidence: 79%
“…A recent study demonstrated that significant differences exist in the frequency of KIR3DL1, 2DS4, 2DS1 and 2DS5 genes in 10 Han Chinese populations form different regions in China ( 47 ). This suggests that investigators who have considered the differences between ethnic groups, but have not considered the differences in geographical regions, may form mistaken conclusions when analyzing the correlations between KIR and disease.…”
Section: Discussionmentioning
confidence: 99%